2018
DOI: 10.1111/jcpp.12920
|View full text |Cite
|
Sign up to set email alerts
|

A multicohort, longitudinal study of cerebellar development in attention deficit hyperactivity disorder

Abstract: Across four independent cohorts, containing predominately longitudinal data, we found diagnostic differences in the growth of cerebellar white matter. In ADHD, slower white matter growth in early childhood was followed by faster growth in late childhood. The findings are consistent with the concept of ADHD as a disorder of the brain's structural connections, formed partly by developing cortico-cerebellar white matter tracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
5
27
0
Order By: Relevance
“…Case-control differences were not significant in adult males. This result corroborates the earlier findings that developmental brain-structural differences observed with MRI in ADHD may normalize in adulthood (11,28,29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Case-control differences were not significant in adult males. This result corroborates the earlier findings that developmental brain-structural differences observed with MRI in ADHD may normalize in adulthood (11,28,29).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, four communities were observed in boys with and without ADHD and in men with ADHD, while in healthy men, only three communities were present. It seemed like community structure in healthy men simplified from four to three communities, whilst patients retained a four-community distribution; this may be consistent with findings of delayed maturation in ADHD (11,28,29), but more research in longitudinal samples is clearly needed.…”
Section: Discussionsupporting
confidence: 73%
“…The ENIGMA-ADHD WG was the first WG in ENIGMA to perform a detailed investigation of the casecontrol effects on the cerebellum. Differential age trajectories were identified for children with ADHD when compared with typically developing children for the corpus medullare 93 .…”
Section: Enigma-attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…Because peers trigger socioemotional brain systems by activating reward-related regions like the ventral striatum (Chein et al, 2011 ; Gardner & Steinberg, 2005 ; Somerville, 2013 ), and peer presence is associated with an increase in the subjective value of immediate rewards (Albert et al, 2013 ), more cognitive control is required to control behavior in the presence of peers. As ADHD is characterized by pronounced inhibitory deficits and a delay in cortical maturation (Barkley, 1997 ; Lijffijt et al, 2005 ; Rubia et al, 2005 ; Shaw et al, 2007 , 2018 ), it follows that a larger imbalance between these brain systems is to be expected in this group (Sonuga-Barke, 2003 ), potentially making adolescents with ADHD unusually susceptible to peer influence.…”
Section: Introductionmentioning
confidence: 99%